Digital Education for Students of LBBP D’King Study, Kramat Jati, East Jakarta - Lydia Kurniawan; Henni Handari; Tikkos Sitanggang; Malik Hidayat; Yopie Yulius; Aang Syahdina; Swesti Mahardini (Universitas Muhammadiyah Malang, 2024)
This community service activity was carried out in collaboration with lecturers from STIE YAI, students, and teaching staff at LBBP (Lembaga Bimbingan Belajar Pelajar) D’King Study in Kramat Jati, East Jakarta. The implementation methods included lectures, discussions, Q&A sessions, and training on the use of digital technology in learning activities as an effort to transform education and realize